An intra-organizational perspective on supply management involvement in contracting services. Issue 5 (December 2020) - de Carvalho Pereira, Gustavo Menoncin; Farias Pereira, Susana Carla; Cooper, Martha C.; Gardner, John T.
Abstract: The relationship between an agent (supply management) and a principal (client functional user) can be studied by using agency theory as a theoretical background. In this study, perceptions of conflict, information asymmetry and risk were examined in relation to perceptions of internal outcomes of supply management's involvement in services contracting in an intra-organizational dyadic context. Structural equation modeling and regression analysis were used to analyze the nature of the relationships. The contribution is integrating a structured view of internal outcomes with three concepts from agency theory to help build a more comprehensive theory of intra-organizational relationships in the context of services contracting. Highlights: Linkage between agency theory concepts and meaningful involvement. Risk/Information asymmetry: significant on positive outcomes of involvement. The structured internal outcomes of SM meaningful involvement in services contracting. Dynamic framework for the temporal effects that drive meaningful involvement. Improve SM involvement with client departments of services purchasing.